QT PRODACT: Evaluation of the Potential of Compounds to Cause QT Interval Prolongation by Action Potential Assays Using Guinea-Pig Papillary Muscles - Yoshihide Kii; Seiji Hayashi; Mitsuyasu Tabo; Takashi Shimosato; Hitoshi Fukuda; Tetsuji Itoh; Hideto Amano; Mamoru Saito; Hajime Morimoto; Kiyoshi Yamada; Atsuhiro Kanda; Toshimasa Ishitsuka; et al. (Elsevier, 2005)
Certain compounds that prolong QT interval in humans have little or no effect on action-potential (AP) duration used traditionally, but they inhibit rapidly-activated-delayed-rectifier potassium currents (IKr) and/or human ether-a-go-go-related gene (hERG) currents. In this study using isolated guinea-pig papillary muscles, we investigated whether new parameters in AP assays can detect the inhibitory effects of various compounds on IKr and/or hERG currents with high sensitivity. The difference in AP duration between 60% and 30% repolarization, 90% and 60% repolarization, and 90% and 30% repolarization (APD30-60, APD60-90, and APD30-90, respectively) were calculated as the new parameters. All the 15 IKr and/or hERG current inhibitors that have been reported (9 compounds) or not reported (6 compounds) to inhibit calcium currents prolonged APD30-60, APD60-90, and/or APD30-90; and 8 of the 15 inhibitors prolonged APD30-60, APD60-90, and/or APD30-90 more potently than APD90. The APD30-60, APD60-90, and APD30-90 measurements revealed no difference in sensitivity when evaluating the effects of the IKr and/or hERG current inhibitors on the three parameters. On the other hand, compounds with little or no effect on hERG currents had no effect on APD30-60, APD60-90, or APD30-90. Therefore, it is concluded that in AP assays using isolated guinea-pig papillary muscles, APD30-60, APD60-90, and APD30-90 are useful indexes for evaluating the inhibitory effects of compounds including mixed ion-channel blockers on IKr and/or hERG currents.Supplementary material (Appendix): available only at http://dx.doi.org/10.1254/jphs.QT-C8 Keywords:: action-potential duration (APD) between 30% and 60% repolarization (APD30-60), APD60-90, APD30-90, human ether-a-go-go-related gene (hERG) current, QT PRODACT